Factors Related to Incident Dengue Hemorrhagic Fever (DHF) - Sekar Arin Nastiti; Karina Nur Ramadanintyas; Avicena Sakufa Marsanti (Jurnal Kesehatan Prima, 2021)
At the present, the Dengue Hemorrhagic Fever (DHF) is one of health problem in Indonesia. In last three years, the incident of DHF in Puskesmas Klagenserut has been significant increase of 17% cases. This research purpose is to know some factors related to with incident DHF in working area Puskesmas Klagenserut. In this research, the researcher uses descriptive quantitative research as approach. The method of research is analytical survey while the type of research is case control. In collecting the data, the researcher uses questionnaires. In analyzing the data, the researcher uses Chi-Square test and regresi logistic test. The sampling technique uses a Total Sampling. The population and samples is all sufferers of January – December 2020 period with 21 respondent cases and 21 respondent control. The result of bivariate test shows that there is a significant correlation between independent variable which is attitude (p-value = 0,045), perception (p-value = 0,022), health facilities (p-value = 0,008), and cadre support (p-value = 0,045), while variable that has no significant correlation is knowledge (p-value = 0,053). Multivariate test result got there is no related variable with incident DHF at working area Puskesmas Klagenserut. The conclusion represents that is related to the attitude, perception, health facility, and cadre support with incident of DHF at working area Puskesmas Klagenserut. Suggestions for further researchers are expected to be able to analyze other risk factors such as environmental conditions and the habit of hanging clothes against the incidence of DHF.